Chemometric perspectives on plankton community responses to natural iron fertilisation over and downstream of the Kerguelen Plateau in the Southern Ocean - Trull, TW; Diana Davies; Dehairs, F; Cavagna, AJ; Lasbleiz, M; Emmanuel Laurenceau; D'Ovidio, F; Planchon, F; Leblanc, K; Queguiner, B; Blain, S (2015)
We examined phytoplankton community responses to natural iron fertilisation at 32 sites over and downstream from the Kerguelen Plateau in the Southern Ocean during the austral spring bloom in October–November 2011. The community structure was estimated from chemical and isotopic measurements (particulate organic carbon – POC; 13 C-POC; particulate nitrogen – PN; 15 N-PN; and biogenic silica – BSi) on size-fractionated samples from surface waters (300, 210, 50, 20, 5, and 1 μm fractions). Higher values of 13 C-POC (vs. co-located 13 C values for dissolved inorganic carbon – DIC) were taken as indicative of faster growth rates and higher values of 15 N-PN (vs. co-located 15 N-NO 3 source values) as indicative of greater nitrate use (rather than ammonium use, i.e. higher f ratios). Community responses varied in relation to both regional circulation and the advance of the bloom. Iron-fertilised waters over the plateau developed dominance by very large diatoms (50–210 μm) with high BSi / POC ratios, high growth rates, and significant ammonium recycling (lower f ratios) as biomass built up. In contrast, downstream polar frontal waters with a similar or higher iron supply were dominated by smaller diatoms (20–50 μm) and exhibited greater ammonium recycling. Stations in a deep-water bathymetrically trapped recirculation south of the polar front with lower iron levels showed the large-cell dominance observed on the plateau but much less biomass. Comparison of these communities to surface water nitrate (and silicate) depletions as a proxy for export shows that the low-biomass recirculation feature had exported similar amounts of nitrogen to the high-biomass blooms over the plateau and north of the polar front. This suggests that early spring trophodynamic and export responses differed between regions with persistent low levels vs. intermittent high levels of iron fertilisation.